2002
DOI: 10.1118/1.1463062
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance in stereotactic space. A system test for verifying the accuracy of aim in radiosurgery

Abstract: A detailed quality assurance (QA) program is essential for high precision single dose irradiations. The accuracy of stereotactic radiosurgery is limited by the errors of each step in the chain for optimal treatment beginning with the diagnostic imaging and target localization leading to the dose planning and ending up with the treatment of the patient. Two main goals were followed on the way to finding a concept for a suitable and sufficient quality assurance routine. First, the chain of items in terms of a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 11 publications
1
38
1
1
Order By: Relevance
“…Another study included lung and liver metastases (7). Most of these papers concluded that radiosurgery was well tolerated and feasible (2,3,5,6). Salazar et al (4) found a high degree of local control and possibly improved survival with the use of radiosurgery; however, a significant percentage of their patients also received conventional external-beam radiation therapy followed by a radiosurgery boost.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study included lung and liver metastases (7). Most of these papers concluded that radiosurgery was well tolerated and feasible (2,3,5,6). Salazar et al (4) found a high degree of local control and possibly improved survival with the use of radiosurgery; however, a significant percentage of their patients also received conventional external-beam radiation therapy followed by a radiosurgery boost.…”
Section: Resultsmentioning
confidence: 99%
“…The patient numbers are small, ranging from 10 to 45 (2)(3)(4)(5)(6). Some studies included both medically inoperable stage I NSCLC and lung metastases (4,6).…”
Section: Resultsmentioning
confidence: 99%
“…The second category refers to inaccurate definition of the target which results from erroneous imaging technique selection, inappropriate interpretation of the images, or geometrical inaccuracies of the scans due to distortion or other technical factors (3) . This latter error has been well described and is usually assessed in standard QA procedures (4) . The third source of error, which is the main scope of this study, is the possibility that the actual location of a target within the stereotactic system at treatment differs from its calculated location due to displacement of the reference frame between the imaging procedure and the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies reported in the literature do not adequately answer all the questions pertaining to the practical clinical implementation of the BrainLAB (Feldkirchen, Germany) frameless SRS system (Novalis), particularly in terms of the overall accuracy of the whole treatment chain, as emphasized in Mack et al (8) …”
Section: Introductionmentioning
confidence: 99%